2020
DOI: 10.1097/rlu.0000000000003410
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-PSMA SPECT/CT Versus 68Ga-PSMA PET/CT in the Evaluation of Metastatic Prostate Cancer

Abstract: Background 99mTc–prostate-specific membrane antigen (PSMA) SPECT/CT is less expensive and readily available modality compared with 68Ga-PSMA PET/CT for imaging prostate cancer (PC). The aim of this study is to compare the value of these 2 modalities in patients confirmed or suspicious to have metastatic prostate cancer. Patients and Methods Twenty-two patients with the mean age of 66.6 ± 10.1 years were studied using 99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…The prostate-specific membrane antigen (PSMA) is a transmembrane protein and highly expressed in PC cells [1,4]. Radioligands targeting PSMA are promising agents for the imaging and treatment of PC patients [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The prostate-specific membrane antigen (PSMA) is a transmembrane protein and highly expressed in PC cells [1,4]. Radioligands targeting PSMA are promising agents for the imaging and treatment of PC patients [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Further to this, studies comparing 99m Tc-PSMA SPECT/CT to 68 Ga-PSMA PET/CT have demonstrated how 99m Tc-PSMA SPECT/CT could be a potential substitute for 68 Ga-PSMA PET/CT. 9 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, different PSMA inhibitors were labeled with 99m Tc [ 134 , 135 , 136 , 137 , 138 ]. [ 99m Tc]Tc-PSMA scintigraphy has been investigated for different purposes, such as biochemical recurrence, primary staging, and radio-guided surgery [ 139 , 140 , 141 , 142 , 143 ].…”
Section: Other Agentsmentioning
confidence: 99%